The hidden world within plants: metatranscriptomics unveils the complexity of wood microbiomes. (2nd February 2022) - Nerva, Luca; Garcia, Jadran F; Favaretto, Francesco; Giudice, Gaetano; Moffa, Loredana; Sandrini, Marco; Cantu, Dario; Zanzotto, Alessandro; Gardiman, Massimo; Velasco, Riccardo; Gambino, Giorgio; Chitarra, Walter
Abstract : We adopted a multidisciplinary approach to describe the whole microbial community associated with the wood tissue of plants, identifying the major players associated with 'healthy' or necrotic tissue, including an unprecedented wide viral community. Abstract: The importance of plants as complex entities influenced by genomes of the associated microorganisms is now seen as a new source of variability for a more sustainable agriculture, also in the light of ongoing climate change. For this reason, we investigated through metatranscriptomics whether the taxa profile and behaviour of microbial communities associated with the wood of 20-year-old grapevine plants are influenced by the health status of the host. We report for the first time a metatranscriptome from a complex tissue in a real environment, highlighting that this approach is able to define the microbial community better than referenced transcriptomic approaches. In parallel, the use of total RNA enabled the identification of bacterial taxa in healthy samples that, once isolated from the original wood tissue, displayed potential biocontrol activities against a wood-degrading fungal taxon. Furthermore, we revealed an unprecedented high number of new viral entities ( 120 new viral species among 180 identified) associated with a single and limited environment and with potential impact on the whole holobiont. Taken together, our results suggest a complex multitrophic interaction in which the viral community also plays a crucial role in raising new ecological questions for the exploitation of microbial-assisted sustainable agriculture.